The effect of IMF and World Bank programmes on poverty - William Easterly (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Structural adjustment, as measured by the number of adjustment loans from the IMF and World Bank, reduces the growth elasticity of poverty reduction. Growth does reduce poverty, but I find no evidence for a direct effect of structural adjustment on growth. Instead, the poor benefit less from output expansion in countries with many adjustment loans than in countries with few adjustment loans. By the same token, the poor suffer less from an output contraction in countries with many adjustment loans than in countries with few adjustment loans. Higher adjustment lending seems to act in a way similar to higher inequality in lowering the stake of the poor in aggregate growth. Why would this be? One hypothesis that adjustment lending is counter-cyclical in ways that smooth consumption for the poor. There is evidence that some policy variables under adjustment lending are counter-cyclical, but there is no evidence that the cyclical component of those policy variables affects poverty. I speculate that the poor may be illplaced to take advantage of new opportunities created by structural adjustment reforms, just as they may suffer less from the loss of old opportunities in sectors that were artificially protected prior to reforms. – poverty ; structural adjustment ; economic growth ; income distribution
Keywords: I3; O1; F4; 330; Anpassungsprogramm des IWF; Armut; Wirkungsanalyse; Welt